2019
DOI: 10.3389/fendo.2019.00157
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Inhibits Inflammation-Induced Osteoclast Formation and Bone Resorption in vivo Through GPR120 by Inhibiting TNF-α Production in Macrophages and Directly Inhibiting Osteoclast Formation

Abstract: Docosahexaenoic acid (DHA) is an n-3 fatty acid that is an important structural component of the cell membrane. DHA exerts potent anti-inflammatory effects through G protein-coupled receptor 120 (GPR120), which is a functional receptor for n-3 fatty acids. DHA also regulates osteoclast formation and function. However, no studies have investigated the effect of DHA on inflammation-induced osteoclast formation in vivo. In the present study, we investigated whether DHA influences osteoclast formation, bone resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Thrombin is the natural ligand of F2r [40,41]. Currently, GPCRs remain a major target for bone related diseases drug discovery [38,39,42,43]. F2r has been the object of large-scale drug development programs since the 1990s, and Vorapaxar and drotrecogin-α are approved F2rtargeted therapeutics [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin is the natural ligand of F2r [40,41]. Currently, GPCRs remain a major target for bone related diseases drug discovery [38,39,42,43]. F2r has been the object of large-scale drug development programs since the 1990s, and Vorapaxar and drotrecogin-α are approved F2rtargeted therapeutics [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed, and they include the regulation of osteoclast and osteoblasts genesis via PPAR and COX/LOX metabolites [ 50 ]. More recently, data have shown that n- 3 LC-PUFA supplementation can potentiate mesenchymal stem cell differentiation and increased osteogenesis [ 51 ], suppress human monocytes-derived osteoclasts formation via PPARs receptors [ 52 , 53 ], inhibit osteoclasts formation and bone resorption through GPR120 receptor [ 54 ], or inhibit RANK-L-induced osteoclasts formation [ 55 ]. In human, studies majoritarily showed that enriched n- 3 LC-PUFA diets are associated with benefits for bone health, and these data have been essentially reported in postmenopausal women in an osteoporosis context [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum CTX levels were assessed using a mouse CTX assay kit (IDS, Boldon, UK). After the assay reaction, each well was evaluated by measuring absorbance at 450 nm with a microplate reader (Remote Sunrise; Tecan, Japan) with a reference wavelength of 620 nm as previously reported [ 41 ].…”
Section: Methodsmentioning
confidence: 99%